2015
DOI: 10.5194/piahs-372-385-2015
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sensors applied to monitorland subsidence in Central Taiwan

Abstract: Abstract. During 1992During -2013, pumping of groundwater caused large-scale aquifer-system compaction and land subsidence in the Choshui River Alluvial Fan (CRAF) in Taiwan. The subsidence has already endangered the operation of Taiwan High Speed Rail (THSR). In this paper, we introduce the multiple sensors monitoring system to study the extent of subsidence in CRAF and its mechanism, including GPS (Global Positioning System), PSI (Persistent Scatterer Interferometry), leveling and multi-layer compaction mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…thus, suitable for distinguishing between various factors that determine subsidence over a compacting aquifer and that act at different depth intervals 145 . To measure the compaction of layers at different depths within a single borehole, an extensometer can include an array of spider magnets anchored at each depth, the readings of which refer to the top or bottom of the borehole 146 .…”
Section: Sea Surface Geoidmentioning
confidence: 99%
“…thus, suitable for distinguishing between various factors that determine subsidence over a compacting aquifer and that act at different depth intervals 145 . To measure the compaction of layers at different depths within a single borehole, an extensometer can include an array of spider magnets anchored at each depth, the readings of which refer to the top or bottom of the borehole 146 .…”
Section: Sea Surface Geoidmentioning
confidence: 99%
“…On the contrary, if the major compaction occurs at a shallow stratum, agricultural water is the main source of water use. (Hung et al., 2015: 388)In 2002, the WRA published a report which revealed that land subsidence of 4 centimetres per year was observed along the planned, high-speed routes in Yunlin County. Politicians immediately held a press conference in which they maintained that the land subsidence would pose potential risk to the high-speed rail infrastructure.…”
Section: Securing the Subterranean Volumes: Modern Geological Knowledmentioning
confidence: 99%
“…On the contrary, if the major compaction occurs at a shallow stratum, agricultural water is the main source of water use. (Hung et al., 2015: 388)…”
Section: Securing the Subterranean Volumes: Modern Geological Knowledmentioning
confidence: 99%
See 1 more Smart Citation